Modelling Mover/Stayer Characteristics across the Life Course Using a Large Commercial Sample. Issue 6 (30th June 2015) - Thomas, Michael; Stillwell, John; Gould, Myles
Abstract: This paper reports the results of logistic regression models for four consecutive age groups in order to capture variations in the characteristics of movers and non‐movers across the life course. The increasing availability of new/alternative sources of microdata, such as Acxiom Ltd's Research Opinion Poll, provides an opportunity to uncover a series of directional associations for covariates that have been largely untested in existing empirical literature. Analysis shows how certain key associational patterns of demographic, socio‐economic, housing, and neighbourhood characteristics vary across life‐course stages. Whilst the empirical results confirm findings from the literature, they also provide new insights into the relevance of subjective neighbourhood satisfaction, suggesting that across the life course, satisfaction is particularly marked for those who have recently moved, a pattern that happens to be further amplified if the mover is a homeowner. © 2015 The Authors. Population, Space and Place published by John Wiley & Sons Ltd.